Insoluble Nano-powders Additives Enhancing the Flow of Liquid in Microchannel: Effect of Particle Size - Fiona Ling, Wang Ming; Abdulbari, Hayder A.; Noraishah, Abdul Latip; Heidarinik, Somaye (Asian Research Publishing Network (ARPN), 2016)
Drag reduction which is first introduced by Toms is now greatly applicable in many fields. Polymers and surfactants are additives that are widely used as drag reducing agents in industries and researches nowadays. Insoluble Nano-powder additives, in the present research, are introduced to enhance the flow of liquid in microchannel. Investigation on the effect of variable concentration (100 to 500 ppm) of three different sizes (7 nm, 200-300 nm and 500-700 nm) Fumed Silica (SiO2) with 100 μm micro-channels by varying the flow rate, using syringe pump, on drag reduction is carried out. Maximum drag reduction up to 56% is achieved using 500 ppm of 200-300 nm fumed silica. This breakthrough discovery will help to speed up the improvement in medical field.